Surrogate-based integrated design of component layout and structural topology for multi-component structures - Bao, Jianwen; Liu, Pai; Zhong, Jiehua; Xu, Yuannan; Luo, Yangjun (Structural and multidisciplinary optimization, 2023)
In the structural and multiphysical design of engineering structures, various functional components with fixed shapes are embedded in a host structure, which poses considerable difficulties in obtaining the optimal structure performance by the simultaneous design of the component layout and structural topology. This study proposes a surrogate-based optimization strategy for the integrated design of component layout and structural topology. In the proposed optimization framework, a multi-component layout is described with a movable material field function by several positional parameters, and the host structure topology is represented by another material field function. The dimension of the topology optimization problem (i.e., the number of design variables) drastically reduces with the material field series-expansion method, while still providing a clear and smooth structural boundary description. Then, a multi-material interpolation model is suggested to couple the host structure and functional components. To avoid the derivation of the sensitivities for complex structural responses and to alleviate the solution difficulty due to the problem’s multiple local solution features, a surrogate-based algorithm based on the sequential Kriging surrogate model is employed to solve the optimization problem. Several numerical examples, including mechanics and electromagnetics design problems, are presented to verify the validity and efficiency of the proposed method.